(3MdHI GdcejJ (B((3aj GdCOH hGdfhGOQ GdeJYdbI HGdNeQjGJ(B)s - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s ((3eMeO Hf CHj HcQ GdaQG s)
(3ChdgG (B:s
(3hHYO(B: (3abO SCdfj ef CeQg eWGY heNGdaJg dG JSJWGY Cf CLeY dg ef ebGWjY GdTYQ fHPI QajYI GdHR, QbjbI GdMGTjI hLeYJ aj gPg GdChQGb eG Qb hQGb hCHQRJ aj hUa GdcejJ TYGQ s
(3BNQgG (B:s
(3hdjS GYJbGO GdeQA eG NW cag ceG Cf MGcj GdcaQ djS HcGaQ hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde, hGdMeO ddg hMOg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B263 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B687s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs